Understanding the Mechanisms of AI-Powered Virtual Assistants: Evaluating Their Impact on Consumer Decision-Making and Brand Loyalty as a Mediating Variable - Istiak, Lazim; Kabir, Ahmed Imran; Sohana, Antara Raisa; Sneha, Humayra Afra Ibnat; Sohel-Uz-Zaman, Abu Saleh Md; Fahad , Abdullah Al (Electronic Journal of Business and Management, 2025)
This research paper looks deeper into the implementation of fundamental AI-driven virtual assistants and estimates their impact on consumer decision-making processes and methods, considering brand loyalty as a leverage or mediating variable. The expansion of AI has led to the incorporation of virtual assistants similar to Google Assistant, Alexa, and Siri into daily life, offering customized assistance and suggestions fabricated to individual choices. These virtual assistants are past basic tasks, assisting consumers in product research and information gathering, suggestions, and decision-making processes. By catering individualized experiences, AI-driven virtual assistants have the ability to enhance loyalty towards brands among consumers. This study talks about and investigates the direct and indirect impacts of AI-powered virtual assistants on consumer decision-making processes, mediated by brand devotion. Literature review highlights the importance of factors such as accuracy of information, time efficiency, cost efficiency, and user experience in forming consumer behavior. Hypotheses are to examine the connection among these variables, which are tested through a mixed method, combining quantitative analysis along with mediation modeling. Findings direct a positive link among AI-run virtual assistants and consumer decision-making, with brand loyalty having a mediating role. Involvement for businesses also includes the improvement of individualized marketing strategies and the maintenance of consumer faith through transparency of AI engagement. Despite the revolutionized influence of AI-powered virtual assistants, constraints such as illustrative collection of data and the need for multiple research techniques and methodologies are recognized, recommending direction for future research to range from the shady dynamics of AI in consumer process of decision-making and brand devotion.